Influence of martensite volume fraction and hardness on the plastic behavior of dual-phase steels: Experiments and micromechanical modeling. (May 2016) - Lai, Qingquan; Brassart, Laurence; Bouaziz, Olivier; Gouné, Mohamed; Verdier, Marc; Parry, Guillaume; Perlade, Astrid; Bréchet, Yves; Pardoen, Thomas
Abstract: Model dual-phase microstructures were developed to decouple the effect of martensite volume fraction and martensite hardness on the plastic behavior of dual-phase steels. The martensite volume fraction ranges from 11% to 37%, involving two levels of martensite hardness. The yield strength and tensile strength increase with increasing martensite volume fraction, while the uniform elongation decreases. The martensite hardness has a weak impact on the initial yield strength, but it significantly affects the flow behavior for sufficiently large martensite volume fraction. Increasing the hardness of the martensite leads to higher tensile strength combined with only a limited impact on uniform elongation, resulting in an improved strength/ductility balance. The experimental results are successfully captured using finite element based micromechanical analysis. Among others, periodic cell calculations show very good predictive capabilities of the overall plastic response when the stage-IV hardening of the ferrite is taken into account. Our numerical analysis reveals that an accurate description of the elasto-plastic behavior of the martensite is a key element to rationalize the mechanical behavior of DP steels. This modeling approach provides a framework for designing dual-phase steels with optimized plastic flow properties. Highlights: Effects of martensite volume fraction and hardness are decoupled experimentally. Higher martensite hardness increases tensile strength without decreasing ductility. Periodic cell model shows good predictive capabilities of the plastic response. The stage-IV hardening of ferrite should be considered to improve the prediction. We show the importance to accurately describe the deformation state of martensite.